Endometriosis-associated infertility: Multi-omics insights into pathogenesis and precision therapeutics - Ou, Yuyi; Wang, Hao; Zhou, Cankun; Chen, Yonglian; Lyu, Jun; Feng, Minqing; Huang, Xiaobin (Frontiers in Endocrinology, 2025)
IntroductionEndometriosis is a prevalent, estrogen-dependent, inflammatory disease that impairs fertility via hormonal dysregulation, immune dysfunction, oxidative stress/ferroptosis, genetic and epigenetic alterations, and microbiome imbalance. We summarize multi-omics insights and clinical implications for endometriosis-associated infertility.MethodsThis article is a Systematic Review that synthesizes recent multi-omics and clinical evidence on mechanisms (hormonal, immune-inflammatory, oxidative stress/ferroptosis, genetic/epigenetic, microbiome/metabolic) and appraises therapeutic strategies spanning surgery, hormonal suppression, assisted reproductive technologies (ART), and emerging adjuncts. Mechanistic and clinical findings are integrated to map targets, biomarkers, and precision-care opportunities across disease phenotypes.ResultsEvidence indicates local estrogen dominance with progesterone resistance, pervasive immune dysregulation, and oxidative stress with iron-driven ferroptosis that particularly injures granulosa cells, alongside disease-relevant genetic/epigenetic regulators and reproductive-tract/gut microbiome dysbiosis. Clinically, endometriosis detrimentally affects ovarian reserve and oocyte competence, disrupts endometrial receptivity/decidualization, and remodels pelvic anatomy through adhesions and fibrosis, cumulatively reducing fecundity. Current management includes laparoscopic excision/ablation, hormonal suppression (e.g., progestins, GnRH analogs/antagonists), and ART tailored to goals and disease severity. Adjunctive antioxidant and immune-modulating approaches show promise but require robust clinical validation. Biomarker discovery—including epigenetic regulators and microbiome-derived signals—may enable earlier diagnosis and personalization. Innovative avenues include immunotherapy targeting nociceptor–immune crosstalk, ferroptosis modulation, microbiota manipulation, and diet-based metabolic strategies.DiscussionThe pathogenesis of endometriosis-associated infertility is multifactorial and interconnected. While current treatments offer benefits, their efficacy is variable. The integration of multi-omics data is unveiling novel diagnostic biomarkers and therapeutic targets. Future management requires a patient-centered, multidisciplinary precision medicine approach that combines mechanistic insights with individualized treatment strategies to improve reproductive outcomes across the disease spectrum.